2004
DOI: 10.1002/ijc.20358
|View full text |Cite
|
Sign up to set email alerts
|

ZNF143 activates gene expression in response to DNA damage and binds to cisplatin‐modified DNA

Abstract: We have identified a cisplatin-inducible gene, the mitochondrial ribosomal protein S11 (MRP S11) gene, by means of mRNA differential display. Functional analysis of the MRP S11 promoter showed that a Staf binding site in the promoter is required for both basal promoter activity and cisplatin-inducible activity. We also found that Cisplatin is a widely used anticancer agent, and DNA damage is believed to be the main basis of the antitumor effect of cisplatin. Since cisplatin resistance is a major obstacle to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 34 publications
0
42
1
Order By: Relevance
“…ZNF143 is a human homolog of Xenopus Staf (Myslinski et al, 1998), and is involved in the transcriptional regulation of small nuclear RNA (snRNA) and snRNA-type genes by RNA polymerase II or III (Schaub et al, 1997;Rincon et al, 1998). It is induced by DNA-damaging agents and binds preferentially to cisplatin-modified DNA (Ishiguchi et al, 2004). In this study, we show that ZNF143 is upregulated in cisplatin-resistant cells.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…ZNF143 is a human homolog of Xenopus Staf (Myslinski et al, 1998), and is involved in the transcriptional regulation of small nuclear RNA (snRNA) and snRNA-type genes by RNA polymerase II or III (Schaub et al, 1997;Rincon et al, 1998). It is induced by DNA-damaging agents and binds preferentially to cisplatin-modified DNA (Ishiguchi et al, 2004). In this study, we show that ZNF143 is upregulated in cisplatin-resistant cells.…”
Section: Introductionmentioning
confidence: 53%
“…p73 stimulates the DNA binding of ZNF143 We previously reported that ZNF143 preferentially binds to cisplatin-modified DNA (Ishiguchi et al, 2004). To examine the effect of p73 on ZNF143 binding to oligonucleotide containing ZNF143 binding site of human U6 RNA promoter and cisplatin-modified DNA, we performed electrophoretic mobility shift assay (EMSA).…”
Section: Association Of P73 With Znf143mentioning
confidence: 99%
See 2 more Smart Citations
“…These data indicate that the acetylation of Sp1 via an interaction with p300 is involved in TAS-103-induced apoptosis in cancer cells. DISCUSSION We have previously identified several transcription factors involved in genomic responses to anticancer agents including Y-box-binding protein-1 (YB-1), activating transcription factor 4 (ATF4), zinc-finger factor 143 (ZNF143), and mitochondrial transcription factor A (mtTFA) (21)(22)(23)(24). This study provides evidence to support the novel finding that Sp1 contributes to the stress response of cancer cells following treatment with anticancer agents.…”
Section: P300 Expression Was Correlated With Sensitivity To Tas-103 Tmentioning
confidence: 99%